A COMPARATIVE STUDY OF THE AGRICULTURAL PRACTICES OF MEMBERS AND NON-MEMBER FARMING COMMUNITY OF MODEL FARM SERVICES CENTER IN KHYBER PAKHTUNKHWA PAKISTAN - T. Shah; J. Tao; c; F. Shah; c; A. Farooq; M. Ishaq; S. B. Khan (Journal of Animal and Plant Sciences, 2016)
The transformation of traditional agriculture into knowledge-based agriculture and shift from cereal to high value agriculture predominantly depends on extension work. So far, many extension programs have been launched to close the existing gap. Model farm service center (MFSC) is a public-private partnership program established in Khyber Pakhtunkhwa (KP) province of Pakistan with the aim to promote agricultural activity and bring progressive changes in the farming communities. The main focus of this study is to investigate the impact of MFSCs on farming and evaluate the farmers’ activities under this program. This study further compares the knowledge, skills, linkages and available facilities of the members and non-member respondents. For data collection four districts namely Swat, Mardan, Abbottabad and Dera Ismail Khan (D.I Khan) were purposely selected. From each of these four districts 120 respondents i.e. 60 member and 60 non-member farmers were randomly selected for data collection. SPSS statistical software was used for data analysis. Results of the study show that most of the farmers are of about 45 years of age or below and their main source of income is from agriculture. Most of these respondents stay in direct contact with the agriculture office for improving their skills and knowledge regarding agriculture. Results of the study further reveal that agricultural agents regularly visit their areas/farms. Most of the respondents use their own agricultural machinery during farming and cultivate their own or fellow farmer seed instead of buying it from MFSC or other input dealers. It is also found that the yield of member respondent is more than that of non- member respondents.
Keywords: Agriculture; Extension services; Farm inputs; Crop yield